Anti-Viral Properties of Amyloid-β Peptides - Bourgade, Karine; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamàs (Journal of Alzheimer's disease, 2016)
Amyloid-β (Aβ) peptides generated by the amyloidogenic pathway of amyloid-β protein precursor processing contribute significantly to neurodegeneration characteristic of Alzheimer's disease (AD). The involvement of Aβ peptides in the etiology of AD remains a subject of debate. Data published in the last 6 years by three different groups have added a new twist by revealing that Aβ peptides could act as antimicrobial peptides (AMP) in in vitro assays against some common and clinically relevant microorganisms, inhibit replication of seasonal and pandemic strains of influenza A and HSV-1 virus. These observations are of significance with respect to the notion that pathogens may be important contributors to the development of AD, particularly in the case of herpes simplex virus (HSV) infection, which often resides in the same cerebral sites where AD arises. Here, we review the data that support the interpretation that Aβ peptides behave as AMP, with an emphasis on studies concerning HSV-1 and a putative molecular mechanism that suggests that interactions between Aβ peptides and the HSV-1 fusogenic protein gB lead to impairment of HSV-1 infectivity by preventing the virus from fusing with the plasma membrane. A number of avenues for future research are suggested.